Letter - Winstanley, E.
030-0158-001 Telegraphic Address, Inland - "Wholesale, Manchester." Foreign - "Copexport, Manchester." Telephone: Blackfriars 1212. Extension No. 87 Please address your reply: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. Cable codes: A.B.C. 6th and 7th editions; Western Union 8 Letter; Bentley Complete Phrase; Bentley Second Phrase; A.I. Marconi, and private. Our reference EXPORT ST/HP. 1179 Your reference 20th June, 1938. The Trades Union Congress, Transport House, Smith Square, LONDON S.W.1. Dear Sirs, Further to our letter of today's date, regarding the goods you have ordered for despatch to Spain on account of the International Solidarity Fund, we intend to effect insurance on this consignment up to the Spanish Frontier, but it will not be possible for the cover to be made effective after this point. Furthermore, it is only possible for us to cover against war risks while the goods are in transit on the sea. Between Rouen and Cerbere insurance will merely be effective against theft, pilferage etc. Respecting the Soap, owing to internal arrangements, it will be necessary for us to invoice through the Co-operative Union Ltd. as previously, although this will not have any effect on the price. Meanwhile, we remain, Yours faithfully, E. Winstanley Export Department. 292/946/30/158